An improved mixed numerical-experimental method for stress field calculation - Lopes, H. (2010)
In this work a numerical-experimental method is used to study the dynamic behavior of an aluminum plate subjected to a small mass impact.The out-of-plane displacements,due to transient bending wave propagation,were assessed for successive time instants,using double pulse TV-holography,also known as pulsed ESPI.